Un lugar es cada cosa (2015)
This work deals with the process of investigation regarding Laura Garzón's installation titled "un lugar es cada cosa". The aim of the investigation is to understand what constitutes a home as such and how to replicate some of its qualities, such as temporal distention acquired by the rituality that defines this spaces. For that end, the investigation is centered, mainly, in the eating and drinking tea processes. From that, the author builds a proposition of her own home as a parenthesis, which is what she concludes homes really are.